Editorial dynamics and control of aerospace and vertical transportation systems - Balthazar, José M.; Gonçalves, Paulo B.; Kaczmarczyk, Stefan; Fenili, André; Silveira, Marcos [UNESP]; Navarro, Ignacio Herrera (Trans Tech Publications, 2014)
This Special Issue presents a selection of papers initially presented at the 11th International Conference on Vibration Problems (ICOVP-2013), held from 9 to 12 September 2013 in Lisbon, Portugal. The main topics of this Special Issue are linear and, mainly, nonlinear dynamics, chaos and control of systems and structures and their applications in different field of science and engineering. According to the goal of the Special Issue, the selected contributions are divided into three major parts: “Vibration Problems in Vertical Transportation Systems”, “Nonlinear Dynamics, Chaos and Control of Elastic Structures” and “New Strategies and Challenges for Aerospace and Ocean Structures Dynamics and Control”.